Analysis of the Impact of Changing Rainfall Zones on Vegetation Cover Variation in Hadhramout Valley, Yemen, Using Geographic Information Systems (GIS) and Remote Sensing (RS) (Libya Journal of Geographical Studies, 2025)
Rainfall is a major climatic element that varies over time and space, influencing the vegetation environment. This study aimed to analyse the effect of shifting rainfall zones on the variation in vegetation cover area in Hadhramout Valley. To highlight this impact, the study utilised Geographic Information Systems (GIS) and Remote Sensing (RS) technologies by applying the Normalized Difference Vegetation Index (NDVI).                The study identified a change in rainfall amounts in Hadhramout Valley from 1983 to 2022, which influenced shifts and changes in the size of rainfall zones. Specifically, the third (60 – 90 mm) and fourth zones (over 90 mm), which received the highest rainfall, experienced a reduction in area during the second and third study periods, following a high coverage in the first period, indicating a trend toward decreasing rainfall. In the fourth period, the area of these zones increased, although they were still smaller compared to the first, rainier period. This decrease affected the vegetation cover area in Hadhramout Valley. The NDVI indicated that dense and moderate vegetation cover occupied no more than 0.5% of the total valley area. Vegetation cover was highest in 1990 but decreased in the second and third study years (2000 and 2011) due to reduced rainfall, before increasing again in 2022, though still less than in 1990.
Keywords: Rainfall Zones; Normalized Difference Vegetation Index (NDVI); Hadhramout Valley